Camarillo State Hospital Governor's Council Report - F.H. Garrett:::::: (1960)
This five page document is the governor's council report for the month of July written by F.H. Garrett, to report the major effort of preparing for the new program that involves admissions. The report also discusses on how Unit II has been having unauthorized absences due to the mentally ill patients interpreting adequate supervision in terms of proper attention. The third topic covered in this report in the rehabilitation therapies department where cooperative effort occurs by volunteer services, nursing services, and patients' account. The report also includes the progress in the farm production which patients work on harvesting crops to maintain the hospital food sources.